A more perfect union : a new vision for building the beloved community - Taylor, Adam, 1976- (Broadleaf Books, 2021)
America is at a pivotal spiritual and political crossroads. A new public narrative is needed to counter the discord in our politics and culture, a new way forward rooted in Martin Luther King Jr.'s vision of the beloved community. In A More Perfect Union, Adam Russell Taylor, president of Sojourners, calls for a shared moral vision that transcends partisanship to live out our nation's best ideals and realize a more perfect union.